Effects of additives on the cure kinetics of vinyl ester pultrusion resins. (September 2021) - Vedernikov, Alexander; Nasonov, Yaroslav; Korotkov, Roman; Gusev, Sergey; Akhatov, Iskander; Safonov, Alexander
Pultrusion is a highly efficient composite manufacturing process. To accurately describe pultrusion, an appropriate model of resin cure kinetics is required. In this study, we investigated cure kinetics modeling of a vinyl ester pultrusion resin (Atlac 430) in the presence of aluminum hydroxide (Al(OH)3 ) and zinc stearate (Zn(C18 H35 O2 )2 ) as processing additives. Herein, four different resin compositions were studied: neat resin composition, composition with Al(OH)3, composition comprising Zn(C18 H35 O2 )2, and composition containing both Al(OH)3 and Zn(C18 H35 O2 )2 . To analyze each composition, we performed differential scanning calorimetry at the heating rates of 5, 7.5, and 10 K/min. To characterize the cure kinetics of Atlac 430, 16 kinetic models were tested, and their performances were compared. The model based on then th-order autocatalytic reaction demonstrated the best results, with a 4.5% mean squared error (MSE) between the experimental and predicted data. This study proposes a method to reduce the MSE resulting from the simultaneous melting of Zn(C18 H35 O2 )2 . We were able to reduce the MSE by approximately 34%. Numerical simulations conducted at different temperatures and pulling speeds demonstrated a significant influence of resin composition on the pultrusion of a flat laminate profile. Simulation results obtained for the 600 mm long die block at different die temperatures (115, 120, 125, and 130 °C) showed that for a resin with a final degree of cure exceeding 95% at the die exit, the maximum difference between the predicted values of pulling speed for a specified set of compositions may exceed 1.7 times.